1978
DOI: 10.1039/c39780000311
|View full text |Cite
|
Sign up to set email alerts
|

A mild, regiospecific but-2-enolide synthesis and a convenient preparation of acylated dienes

Abstract: Phase transfer-catalysed, cobalt carbonyl-catalysed reaction of alkynes with carbon monoxide and methyl iodide affords but-2-enolides ; acylation occurs if dienes instead of alkynes are used as reactants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…(60)]. [125] Recently, it has been reported that the nickel-catalyzed carbonylation of a-haloalkynes with carbon monoxide under phase-transfer conditions gave either allenic monoacids or unsaturated diacids. It was shown that the carbonylation afforded monoacids first, and then gave diacids with high stereoselectivity [Eq.…”
Section: Carbonylationmentioning
confidence: 99%
“…(60)]. [125] Recently, it has been reported that the nickel-catalyzed carbonylation of a-haloalkynes with carbon monoxide under phase-transfer conditions gave either allenic monoacids or unsaturated diacids. It was shown that the carbonylation afforded monoacids first, and then gave diacids with high stereoselectivity [Eq.…”
Section: Carbonylationmentioning
confidence: 99%
“…89 The alkynes 176 react smoothly with CO and MeI in a liquid -liquid two-phase system to yield regioselectivly the corresponding but-2-enolides 177 (Scheme 72), most probably via the intermediate formation of an acylcobalt complex. 90,91 When benzyl bromide was used, no but-2-enolide was formed, due to the fast hydrolysis of the acylcobalt intermediate prior to the alkyne complexation, and phenylacetic acid was the only product obtained. This inconvenience was circumvented by performing the reaction in the absence of water in a solid -liquid system using a new kind of chelating agent, N[(CH 2 ) 2 O(CH 2 ) 2 OMe] 3 (TDA), which has the same properties as a crown ether but without the toxicity and the work-up difficulties encountered with the macrocyclic catalysts 92 (Scheme 73).…”
Section: Selective Synthesis Of Furan-2(5h)-onesmentioning
confidence: 98%
“…70 The cis stereochemistry of the reaction is rationalized by assuming that attack of Pd II on the alkene is directed by the allylic OH group, forming the intermediate (12).…”
Section: R~or R~ormentioning
confidence: 99%